STUDY OF THE IMPACT OF THE AUTOMOTIVE INDUSTRY ON THE ENVIRONMENT - Сабирова Дилорам Кабуловна; Ахматова Мадина Юсуф кизи (European Science Publishing, 2023)
This article examines the environmental impacts of the automotive industry, explores its environmental impacts, and explores potential ways to achieve sustainability. The study uses a comprehensive approach that includes literature review, detailed methods, results, and discussion of findings. The findings of this study provide insight into how to reduce the environmental impact of the automotive sector, and offer value propositions for a greener future.
Keywords: Automotive industry, Ecology, Environmental impact, Sustainable transport, emissions, Green technologies, Literature analysis, Methods, Results, Discussion, Conclusions, proposals.